Essential oils and their application on active packaging systems: a review - Carpena Rodríguez, María (2018)
The food industry is continuously evolving through the application of innovative tools and ingredients towards more effective, safe, natural and ecofriendly solutions to satisfy the demands of the costumers. In this context, natural sources (i.e., leaves, seeds, peels or unused pulp) can entail a valuable source of compounds, such as essential oils (EOs), with recognized antioxidant and antimicrobial properties that can be used as natural additives in packaging applications. The current trend is the incorporation of EOs into diverse kinds of biodegradable materials, such as edible films, thus developing active packaging systems with improved preservation properties that can offer benefits to both the food and packaging industry by reducing food waste and improving the management of packaging waste. EOs may be added into the packaging material as free or encapsulated molecules, where, especially this last option, has been revealed as very promising. The addition of these lipophilic compounds provides to the end-product various bioactivities of interest, which can eventually extend the shelf-life of the product by preventing food spoilage. Pairing biodegradable packaging with EOs extracted from natural agro-industrial by-products can lead to a more sustainable food industry. Recent knowledge and advances on this issue will be reviewed in the present work.